Hierarchical Similarity Of Context Instances (International Journal of Engineering and Computer Science, 2017)
In this paper we present a methodology for how the contexts are analyzed for the context information finding in terms of web history searching in personal information management system. Context annotation and context degradation for context analysis are presented in the methodology. Hierarchical similarity finding between context attributes and context instances are implemented in this paper.